Literature Study Of Investment Risk Management Implementation In Sharia Banking - Suhartini, Nani; Atiah, Isti Nuzulul; Najib, Mohamad Ainun (Syi`ar Iqtishadi : Journal of Islamic Economics, Finance and Banking, 2023)
A risk is a certain event that has the potential to create a loss. Investment risk in banking is the risk that requires the bank to share in the losses from the customer's business that has been financed in profit-sharing-based financing using the net revenue sharing method and the profit and loss sharing method. This study aims to analyze the determinants of investment risk and its impact on Islamic banking and the implementation of investment risk management in Islamic banking. This study uses a literature study approach to answer the research objectives and the analytical technique used in this research is content analysis. The results of this study found that there were differences in investment risk in Islamic banking, namely mudharabah and musyarakah investment risks.